Plotinus, neoplatonism & the transcendence of the one - Halfwassen, Jens (Theandrites$dstudies on Byzantine philosophy and Christian platonism, 2021)
"Plotinus (204-70) is the founder of Neoplatonism and its most significant thinker. He shaped late antique philosophy and significantly influenced the entire metaphysical tradition of the Middle Ages, Renaissance, and German Idealism. In this volume, Jens Halfwassen presents Plotinus' life and work, as well as the most important aspects of his historical influence. Issues of key importance for the Neoplatonists-such as the interaction between Being and Thought, the ascent of the soul, and the interpretation of Plato's theory of principles-are explained in detail in the course of outlining the Neoplatonic metaphysical system. The introduction outlines Halfwassen's significant contribution to the study of Plotinus, paying particular attention to the differences between the current German and Anglophone approaches to the Platonic tradition"--